Antibacterial and Phytochemical Screening of Artemisia Species - Maria-Evelina Bordean; Rodica Ana Ungur; Dan Alexandru Toc; Ileana Monica Borda; Georgiana Smaranda Marțiș; Carmen Rodica Pop; Miuța Filip; Mihaela Vlassa; Bogdana Adriana Nasui; Anamaria Pop; Delia Cinteză; Florina Ligia Popa; et al. (MDPI AG, 2023)
Taking into account the increasing number of antibiotic-resistant bacteria, actual research focused on plant extracts is vital. The aim of our study was to investigate leaf and stem ethanolic extracts of Artemisia absinthium L. and Artemisia annua L. in order to explore their antioxidant and antibacterial activities. Total phenolic content (TPC) was evaluated spectrophotometrically. Antioxidant activity was evaluated by DPPH and ABTS. The antibacterial activity of wormwood extracts was assessed by minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) in Escherichia coli, Staphylococcus aureus, Listeria monocytogenes, and Salmonella enteritidis cultures, and by zone of inhibition in Klebsiella carbapenem-resistant enterobacteriaceae (CRE) and Escherichia coli extended-spectrum β-lactamases cultures (ESBL). The Artemisia annua L. leaf extract (AnL) exhibited the highest TPC (518.09 mg/mL) and the highest expression of sinapic acid (285.69 ± 0.002 µg/mL). Nevertheless, the highest antioxidant capacity (1360.51 ± 0.04 µM Trolox/g DW by ABTS and 735.77 ± 0.02 µM Trolox/g DW by DPPH) was found in Artemisia absinthium L. leaf from the second year of vegetation (AbL2). AnL extract exhibited the lowest MIC and MBC for all tested bacteria and the maximal zone of inhibition for Klebsiella CRE and Escherichia coli ESBL. Our study revealed that AbL2 exhibited the best antioxidant potential, while AnL extract had the strongest antibacterial effect.